2020
DOI: 10.1186/s12935-020-01218-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of cancer stem cells in the development of giant cell tumor of bone

Abstract: The primary bone tumor is usually observed in adolescence age group which has been shown to be part of nearly 20% of the sarcomas known today. Giant cell tumor of bone (GCTB) can be benign as well as malignant tumor which exhibits localized dynamism and is usually associated with the end point of a long bone. Giant cell tumor (GCT) involves mononuclear stromal cells which proliferate at a high rate, multinucleated giant cells and stromal cells are equally present in this type of tumor. Cancer stem cells (CSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 133 publications
(133 reference statements)
0
15
0
Order By: Relevance
“…It is important to note that Atxn2 -mutations were already observed to affect cholesterol homeostasis and trigger gender-dependent or hormonal effects [ 31 , 73 , 96 , 97 ]. Giant multinucleated cells can be due to increased mTOR activity [ 98 , 99 , 100 ]. Given that ATXN2 was reported to inhibit mTOR in yeast, nematodes and mice; also the absence of ATXN2L might lead to enhanced mTOR signaling and, in this way, increase the appearance of multinucleated giant cells in MEF cultures.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that Atxn2 -mutations were already observed to affect cholesterol homeostasis and trigger gender-dependent or hormonal effects [ 31 , 73 , 96 , 97 ]. Giant multinucleated cells can be due to increased mTOR activity [ 98 , 99 , 100 ]. Given that ATXN2 was reported to inhibit mTOR in yeast, nematodes and mice; also the absence of ATXN2L might lead to enhanced mTOR signaling and, in this way, increase the appearance of multinucleated giant cells in MEF cultures.…”
Section: Discussionmentioning
confidence: 99%
“…However, research into the methylation regulation of TGFBI in RC has not been reported. Pathway analysis also revealed that these MeDEGs were enriched in the PI3K-Akt signaling pathway, which was involved in multiple types of malignancies [46,47] , including RC [48] . In the current study, we identi ed many aberrantly methylated and expressed genes participating in the PI3K-Akt signaling pathway, which could provide a foundation for experimental research in RC.…”
Section: Discussionmentioning
confidence: 95%
“…Polyploid giant tumor cells have been pathologically recognized, particularly in bones, for a long time [ 61 , 62 ], and clinical evidence has shown that the incidence and frequency of such tumor cells are significantly associated with the grade, chemoresistance, and poor prognosis of cancer patients [ 63 , 64 ]. Polyploidization is regulated by AURKA [ 65 ], AURKB [ 66 ], and c-MYC [ 67 ], followed by the degradation and inactivation of TP53, which is important for the cell cycle checkpoint.…”
Section: Tumor Regeneration After Emtmentioning
confidence: 99%